Routinely detected indicators in plasma have a predictive effect on the identification of HIV-infected patients with non-tuberculous mycobacterial and tuberculous infections - Ren-tian Cai; Feng-xue Yu; Zhen Tao; Xue-qin Qian; Jun Chen; Hong-zhou Lu (BMC, 2017)
Abstract Background It is difficult to quickly distinguish non-tuberculous mycobacterial (NTM) infection from tuberculosis (TB) infection in human immunodeficiency virus (HIV)-infected patients because of many similarities between these diseases. A simple and effective way to determine the differences using routine blood tests is necessary in developing countries. Methods A retrospective cohort study was conducted to recruit HIV-infected patients with either NTM infection or TB infection diagnosed for the first time according to mycobacterial culture and microscopic identification from May 2010 to March 2016. These data included the analysis of blood cells, liver function, renal function, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR), and were compared between the HIV/TB and HIV/NTM groups. Results A total of 240 patients were enrolled. The number of HIV/TB and HIV/NTM patients was 113 and 127, respectively. There were no significant differences in the CD4 T-cell count, age, sex, percentage of patients initiating antiretroviral therapy (ART) before the explicit diagnosis of TB or NTM infection. NTM infection was more likely to be restricted in the pulmonary while TB infection also involves extra-pulmonary sites. Both the leukocyte count(5.60 × 109/L) and the proportion of neutrophils in the leukocyte count (76.70%) in the HIV/TB group were significantly higher than those in the HIV/NTM group (4.40 × 109/L [P = 0.0014] and 69.30% [P < 0.001]. The analysis of liver function markers indicated that the concentration of albumin but not ALT and AST was significantly lower in the HIV/TB group than in the HIV/NTM group (P < 0.001). The creatinine and urea levels were not significantly different between the two groups. The ESR (84.00 mm/h) and the concentration of CRP (59.60 mg/L) were significantly higher in the HIV/TB group than in the HIV/NTM group (52.00 mm/h and 19.60 mg/L, respectively) (P < 0.001). To distinguish TB infection from NTM infection, the best cut-off value was 69.5 mm/h for ESR, with a positive predictive value (PPV) of 0.740 and negative predictive value (NPV) of 0.721, and 48.8 mg/L for CRP, with a PPV of 0.676 and NPV of 0.697. Conclusion The dissemination character as well as stronger immune response characterized by higher inflammation markers (e.g. WBC, ESR, CRP) can help distinguish TB from NTM infection in HIV-infected patients who need empirical therapy or diagnostic therapy immediately in low-income areas.